THE PERCEPTION OF TECHNOLOGICAL TOOLS USEFULNESS TO DEVELOP MEDICAL CLINICAL SKILLS AMONG POSTGRADUATE MEDICAL STUDENTS (Proceedings of the International Conference on Education, 2022)
COVID-19 pandemic has forced postgraduate medical students to limit clinical practice. This demands clinical training centers to look at how to take advantage of digital resources available in the market to benefit a future doctor's training. Technological resources in healthcare learning and training clinical skills cover three aspects: learning through apps, virtual simulation, and social media. This study aimed to identify popular technological tools that doctors in training used in the Multicentric program at Tecnológico de Monterrey and analyze their valued opinions. An online questionnaire with 20 mixed questions, multiple-choice and open questions, was sent via email to all residents in the program. Answers were anonymous and voluntary of 60 responses received, 48 indicated that the use of digital apps increased during the pandemic. Application of clinical scales and updated information about diseases were the most common reasons to use the applications. 50% of residents mentioned using virtual simulation as a tool, while 20% identified it beneficial for developing clinical skills. It was surprising that most of them considered medical education content from social media such as You Tube® and Twitter® as good quality information. Apps have reached good popularity among residents, but simulation and social media are becoming popular and reliable. Attention has to be turned to these resources, for they may serve as aid tools for healthcare professionals.
Keywords: clinical learning; technology; tools; digital apps; virtual simulation; social media